Marketing As Tool of Resource Efficiency; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 26 : Responsible Research and Innovation (RRI 2016) - Nikulina I. E. Irina Evgenyevna (2017, 2017)
Title screen